Freeman-Sheldon Syndrome Presenting with Microstomia: A Case Report and Literature Review - Gurjar, Vivek (Springer India, 2012)
Freeman-Sheldon syndrome (FSS), as first described by Freeman and Sheldon in 1938, is a morphologically well-defined syndrome that results in a dysmorphic status combining bone anomalies and joint contractures with characteristic facies. It is part of the nosologic group of pathologies currently known as distal arthrogryposis as reported by Hall et al. (Am J Med Genet 11:185–239, 1982 [1]). It is a rare disorder and its exact prevalence is unknown. Our objective is to report a case of FSS presenting with microstomia and add a brief review of the literature for similar cases.